A Note on Planar Hexagonal Meshes - Wang, Wenping; Liu, Yang (Springer New York, 2009)
We study the geometry and computation of free-form hexagonal meshes with planar faces (to be called P-Hex meshes). Several existing methods are reviewed and a new method is proposed for computing P-Hex meshes to approximate a given surface. The outstanding issues with these methods and further research directions are discussed.